Sex differences in ocular biometric measurements: A twin study - Zhang, Han; Zhou, Jing; Yang, Lili; Zhang, Xiaogung; Shi, Wei; Yang, Hailong; Zhang, Guisen; She, Jie; Li, Huixia (Frontiers in Medicine, 2022)
Abstract Objective: Gender differences in ocular biometric measurements of opposite-sex and same-sex twin pairs are still unclear. We aimed to investigate the difference of ocular biometric measurements in adolescent twin pairs. Methods: This retrospective study included a total of 65 eyes of 65 adolescents from 32 twins. The ocular biometric measurements and refractive prediction error (RE) were acquired from four groups of dizygotic (DZ) twins: boys from same-sex twin-pairs (SSM, n = 20), boys from opposite-sex twin-pairs (OSM, n = 8), girls from opposite-sex twin-pairs (OSF, n = 8), and girls from same-sex twinpairs (SSF, n = 29). Results: Mean patient age was 9.92 ± 2.84 (range: 6 - 18) years. Overall, boys had higher height, AL, WTW, but lower Ks, and Kf than those within girls (P < 0.05). Specifically, SSF were found to have the lowest lens thickness (LT), anterior chamber depth (ACD), central corneal thickness (CCT), white to white (WTW) and axial length (AL) levels, while the highest keratometry readings in the flat (Kf) and steep (Ks) levels compared with OSM, OSF and SSM adolescents (P < 0.05). Compared with the OSF adolescents, ACD levels of the SSF adolescents was significantly lower [(2.99 ± 0.35) mm and (3.26 ± 0.15) mm, P = 0.033)], but Kf indicator was significantly larger [(43.93 ± 1.64) and (42.91 ± 1.75), P = 0.016)]. Conclusions: Our study indicates that sharing the uterus with a DZ twin SSF have smaller ocular indicator measurements. Our findings provide information on eyeball and refractive development in adolescents.